Etude des propriétés physiques des sulfures de Fer Fe7S8 et Fe3S4 à l’aide des méthodes de Ab-initio, Monte Carlo et Champ Moyen - Safae Benyoussef (Faculté des Sciences de Rabat, 2021)
Attracted by the interest of new materials in technological development, many studies have been carried out in the field of materials science. Iron sulphides are among the most recently studied materials, due to their use in several fields of application, and the selection of one of these must be according to their requested property for each application. In this context, the study of properties is one of the most necessary scientific challenges in order to match these iron sulfides for adequate applications. Among the minerals of the iron-sulfur system, we have chosen to focus on this study, two of them in particular, they are Pyrrhotite and Greigite.
Study of the physical properties of Fe7S8 and Fe3S4 iron sulphides using Ab-initio, Monte Carlo and Medium Field methods
Keywords: Physique; Physique